Exemption of Nicotine Liquid From the Poison Act 1952: Considerations From the Point of View of Maslahah and Mafsadah - Noor Syifa Mohd Akib; Muhammad Nizam Awang@Ali (Faculty of Syariah and Law, Universiti Sains Islam Malaysia, 2026)
In Malaysia, the majority of vape and cigarette users of young people between the ages of 13 and 18. Despite the harm, the government have decided to remove nicotine-containing products either liquid or gel from the Poison Act of 1952. This has sparked debates among the public, policymakers, politicians, and experts about the law's impact on the next generation as this will allow all products containing nicotine can be legally sold to children of any age. Therefore, this study investigates the nature of nicotine, the position of nicotine under the Poisons Act of 1952, as well as the mafsadah and maslahah considerations of the exemption. This study employs qualitative methodologies and a library-based strategy by collecting data from books, journals, articles, newspapers, and others. In conclusion, our government policies must prioritize maslahah ‘ammah above maslahah khasah and introduce the Generation End Game (GEG) policy sooner to control the consumption of nicotine among young generation.